Meningkatkan Keberanian Memanfaatkan Alat Permainan di Luar Kelas Melalui Bermain Papan Titian Pada Anak Kelompok A TK Pusparita Ngipik Pringsurat Temanggung Semester II Tahun Pelajaran 2017/2018 - parinah parinah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Courage is a quality of character that must be nurtured in children so that children are able to defend what they think is right. The problem faced by children in Group A of Pusparita Ngipik Kindergarten is that children's courage is still low. The purpose of this study was to find out how to increase children's courage by using game tools outside the classroom by playing the catwalk and to find out the magnitude of the increase in the courage of group A children in Pusparita Ngipik Pringsurat Temanggung Kindergarten Semester II 2017/2018 Academic Year. The subjects of this study were 19 students in Group A of Pusparita Ngipik Kindergarten. The research was carried out in February 2018. The data collection methods used were observation, documentation and interviews. Based on the results of the research and discussion, it can be concluded that utilizing outdoor game tools through playing the catwalk can increase the courage of children in Group A TK Pusparita Ngipik Pringsurat Temanggung Semester II for the 2017/2018 academic year with the results of observing children's courage in pre-cycle conditions of 26.3 %, increased to 47.4% in Cycle I, and increased in Cycle II with a percentage value of 89.5% marked by the achievement of predetermined success indicators, namely the child is able to walk on a catwalk by holding onto a stick, stretching out both hands like an airplane. , hands on waist and walk sideways